The impact of the nutritional gap of poultry meat and table eggs in achieving food security in Iraq for the period 1997-2007 (Journal of the College of Basic Education, 2022)
The results of the economic analysis showed that the poultry industry in Iraq witnessed a significant deterioration during the decade of the nineties until production reached in 1997 (3.8) thousand tons of poultry meat and (4.9) million table eggs, which forced the state to intervene at the end of 1997 to save this vital industry to support Producers and breeders and restoring the destroyed circles through the Poultry Projects Rehabilitation Program, which was supervised by the Ministry of Agriculture in cooperation with the International Food and Agriculture Organization (FAO). The industry gradually revived again. In 2002, production reached (106.6) thousand tons of poultry meat and (1059) million eggs. Table, then this industry went through another setback in 2003 due to the occupation, as production declined to (46.3) thousand tons of poultry meat and (604.4) million table eggs, as shown in Table (1), and production remained in a continuous decline until now.